2019
DOI: 10.1101/642819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analyses reveal aberrant pathways for megakaryocyte-biased hematopoiesis in myelofibrosis and identify mutant clone-specific targets

Abstract: Myelofibrosis is a severe myeloproliferative neoplasm characterised by increased numbers of abnormal bone marrow megakaryocytes that induce progressive fibrosis, destroying the hematopoietic microenvironment. To determine the cellular and molecular basis for aberrant megakaryopoiesis in myelofibrosis, we performed high-throughput single-cell transcriptome profiling of 50,538 hematopoietic stem/progenitor cells (HSPCs), single-cell proteomics, genomics and functional assays. We identified an aberrant pathway fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
3
1
Order By: Relevance
“…We found that a subpopulation of immunophenotypic CD34 + CD38 -HSPCs express CD41 and are Mkbiased in colony assays. The frequency of adult CD34 + CD38 -CD41 + progenitor cells (~25%) reported here is higher than prior reports in freshly isolated bone-marrow HSPCs 27,78 , likely due to longer time in HSPC expansion culture media containing fms-like tyrosine kinase 3 ligand (FLT3L), thrombopoietin (TPO) and stem cell factor (SCF), which also promotes Mk differentiation. The lentiviral shRNA approach utilized here achieved ~50-70% reduction of RUNX1 levels in terminal adult Mks, and a Mk yield defect as anticipated.…”
Section: Prior Studies Of Single Cell Transcriptomics Lineage Tracincontrasting
confidence: 80%
“…We found that a subpopulation of immunophenotypic CD34 + CD38 -HSPCs express CD41 and are Mkbiased in colony assays. The frequency of adult CD34 + CD38 -CD41 + progenitor cells (~25%) reported here is higher than prior reports in freshly isolated bone-marrow HSPCs 27,78 , likely due to longer time in HSPC expansion culture media containing fms-like tyrosine kinase 3 ligand (FLT3L), thrombopoietin (TPO) and stem cell factor (SCF), which also promotes Mk differentiation. The lentiviral shRNA approach utilized here achieved ~50-70% reduction of RUNX1 levels in terminal adult Mks, and a Mk yield defect as anticipated.…”
Section: Prior Studies Of Single Cell Transcriptomics Lineage Tracincontrasting
confidence: 80%
“…As predicted, patients with SCD appear to show an increased proportion of cells with an erythroid gene-expression program although this did not reach statistical significance ( Figure 1B; supplemental Table 3) (control, 7.86%; thalassemia, 6.97%; and SCD, 9.67%). No expansion of erythroid gene-expressing cells was seen in children with thalassemia, consistent with adherence to a rigorous regular transfusion protocol designed to suppress endogenous erythropoiesis in these patients ( Trajectory analysis was performed using an in-house R package, 20 which allowed the expanded lymphoid progenitors to be subclassified into early B progenitors, 22 expressing high levels of IL7R and IGHM, and late CD24-expressing B progenitors (supplemental Figure 5; supplemental Tables 1-3). These data were corroborated using multiparameter flow cytometry, which showed significant increases in the frequency of CD34 1 CD10 1 CD19 1 cells in these patients (Figure 1C-D; supplemental Figures 7 and 8; supplemental Table 4).…”
mentioning
confidence: 67%
“…Analysis of scRNA-seq data using Seurat 18 and AUcell 19 (see supplemental Table 2 for quality control data) showed a marked expansion of CD34 1 B-lymphoid progenitors ( Figure 1A-B) in all 8 children with hemoglobinopathies compared with controls (supplemental Figures 1-6). Cells identified as B-lymphoid progenitors were enriched for expression of lymphoid genes 20,21 including CD79A, CD79B, VPREB1, VPREB3, and EBF1 (supplemental Table 3; area under the curve 0.25 was used for all samples). As predicted, patients with SCD appear to show an increased proportion of cells with an erythroid gene-expression program although this did not reach statistical significance ( Figure 1B; supplemental Table 3) (control, 7.86%; thalassemia, 6.97%; and SCD, 9.67%).…”
mentioning
confidence: 99%
“…In contrast, myeloid, erythroid and lymphoid-related genes 13 , including CSF3R, PRTN3, CA1, CNRIP1, APOC1, TFR2, CD4, CD79A and CD79B, were more highly expressed in vehicle/cytokine conditions. Unexpectedly, three of the most upregulated genes in CPI203/cytokine-expanded cells are strongly associated with megakaryocyte (MK) development (CXCR4 17 , PF4 18 and C6orf25 19 ).…”
Section: Cpi203 Promotes Expansion Of Hsc and Megakaryocytesmentioning
confidence: 99%